Improving English Speaking Abilities Using Communicative Language Teaching Approach Through Flashcards in Islamic Boarding School Culture - Fitriyah, Fitrah Yuliawati, Ina Daril Hanna (Lembaga Bale Literasi, 2025)
This study aims to evaluate the effectiveness of the Communicative Language Teaching (CLT) approach, integrated with flashcards based on the culture of Islamic boarding schools, in improving the English speaking skills of tenth-grade students at MA Bustanul Ulum. This study was motivated by the high levels of language anxiety and the lack of contextual learning materials that align with the daily lives of students in boarding schools. This study employed a Classroom Action Research (CAR) design following the Kemmis and McTaggart model across two cycles, involving 16 students selected through purposive sampling. Data were collected via speaking tests, observation sheets, and field notes, and analyzed using descriptive-comparative techniques. The results showed a significant improvement in students’ speaking performance; the class average score increased from 56.5 in the pre-intervention phase to 73.6 in Cycle I and reached 85.4 in Cycle II. Additionally, the percentage of students meeting the learning standards surged from 0% to 100% by the end of the second cycle. The integration of local wisdom into visual media has been shown to reduce psychological barriers and increase students’ active participation. This study implies that contextualizing learning materials with students’ cultural identities is a key factor in the success of EFL teaching in a pesantren environment